A Phase II Study of Tumor Ablation in Patients with Metastatic Sarcoma Stable on Chemotherapy. (27th February 2018) - Hirbe, Angela C.; Jennings, Jack; Saad, Nael; Giardina, Joseph D.; Tao, Yu; Luo, Jingqin; Berry, Shellie; Toeniskoetter, Jacqui; Van Tine, Brian A.
Abstract : Lessons Learned : Ablation therapy appears to be a reasonably safe and effective approach to obtain a significant treatment‐free interval for a subset of patients with limited sites of metastatic disease for which systemic control can be obtained with six cycles of chemotherapy. Background: Metastatic sarcoma often becomes resistant to treatment by chemotherapy. There is sometimes prolonged stable disease from active chemotherapy that provides a window of opportunity for an intervention to prolong disease‐free survival. Materials and Methods: We performed a phase II study in patients with metastatic sarcoma who had been stable on six cycles of chemotherapy who then received ablation therapy to their residual disease. Histologies captured in this study included leiomyosarcoma, malignant peripheral nerve sheath tumor, pleiomorphic rhabdomyosarcoma, and myxoid liposarcoma. Sites ablated included lung metastases and retroperitoneal metastatic deposits. In this study, up to three lesions were ablated in any given interventional radiology session. After ablation, patients were not treated with any further therapy but were followed by surveillance imaging to determine progression‐free rate (PFR). Results: Although terminated early because of slow accrual, this study demonstrated a 3‐month PFR of 75% for this cohort of eight patients treated with ablation performed after completion of six cycles of chemotherapy with stable disease. Median progression‐free survival (PFS) was 19.74 months, and the median overall survival (OS) was not reached. Conclusion: Our data are the first prospective study to suggest that ablation therapy in selected patients who are stable on chemotherapy can provide a significant progression‐free interval off therapy and warrants further study in a randomized trial.